FAKTOR FUNDAMENTAL MAKROEKONOMI, RISIKO SISTEMATIS DAN KINERJA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (Fokus Ekonomi, 2009)
The purpose of this research is to analysis  influence of macroeconomic factors, as inflation, interest rate, exchange rate, economic growth; and systematic risk toward financial performance for 2004 to 2006. This research uses secondary data, with the source of data from BPS and Indonesian Capital Market Directory publication. The sampling technical used purposive sampling, and  total sample is 116 firm with the 348  observation sample. The analysis with regression ordinary least square – OLS. Result the test that inflation and exchange rate are significant negative influence the systematic risk, but interest rate and economic growth are significant positive toward to systematic risk. Interest rate significant positive toward financial performance, and systematic risk is significant negative toward financial performance. Exchange rate significant negative at level less than 10% toward financial performance.  In this research is only interest rate toward systematic risk, and than exchange rate & systematic risk toward financial performance support economic theory. The R-square is 0,031 so the five independent variable is have a weak ability to predict financial performance. The other result that systematic risk is a intervening variable, they are mediation macroeconomic fundamental factor with firm performance.